Integrasi Prinsip ESG (Environmental, Social, Governance) Dalam Perbankan Syariah - Purwanto, Hery (Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to examine the incorporation of Environmental, Social, and Governance (ESG) principles in sharia banking through a qualitative approach based on library research. The research literature is utilized to explore theories, policies, and literature related to ESG implementation in the Islamic banking sector, drawing from various sources such as academic articles, industry reports, and relevant regulations. ESG has emerged as a global trend, urging financial institutions to embrace socially responsible practices. Islamic banking inherently aligns with ESG principles, encompassing values such as justice, social responsibility, and good governance. Despite the harmony between sharia and ESG, this research identifies several challenges in implementing ESG in sharia banking, including compliance with specific regulations, inadequate impact measurement tools, and instances of greenwashing that focus more on specific products like green sukuk and ESG integration. However, there exists a significant opportunity for Islamic banking to enhance ESG integration through the innovation of ESG-based financial products, such as productive waqf, which can support sustainable social and environmental projects. This research provides an original contribution by critically analyzing the challenges of ESG implementation in Islamic banking and offering recommendations to surmount these obstacles. The novelty of this research lies in uncovering the potential for broader ESG implementation in sharia-compliant banking, involving regulators, industry, and society as the main stakeholders. Recommendations also include the development of a more specific regulatory framework and incentives for Islamic banking to comprehensively integrate ESG.